161k views
8 votes
(59-6) x (⅓) ³ + 27 ÷ 3 =

8² ÷ 4 x (2 + 3) -9 =​

User Race B
by
6.5k points

1 Answer

9 votes

Answer:

(59-6) ×
\sf{((1)/(3))}^(3) + 27 ÷ 3

=53 ×
\sf\frac{{1}^(3)}{{3}^(3)} + 3³ ÷ 3

=53 ×
\sf(1)/(27) +
\sf{3}^(3-1)

=
\sf(53*1)/(27) +
\sf{3}^(2)

=
\sf(53)/(27) + 9

=9 +
\sf(53)/(27) + 9

=
\sf(9*27+53)/(27)

=
\sf(243+53)/(27)

=
\sf(296)/(27)

=
\sf(270)/(27)+(26)/(27)

=
\sf10+(26)/(27)

=
\sf10(26)/(27)


\sf\:

8² ÷ 4 × (2 + 3) - 9

=(8×8) ÷ 4 × 5 - 9

=64 ÷ 4 × 5 - 9

=4³ ÷ 4 × 5 - 9

=
\sf{4}^(3-1) × 5 - 9

=4² × 5 - 9

=(4×4) × 5 - 9

=16 × 5 - 9

=80 - 9

=71

User DungeonTiger
by
5.4k points